The amino acid sequence of the tryptic peptides of the f1 bacteriophage coat protein : a thesis submitted to Massey University of the Manawatu in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry - Richardson, Barry Charles (Massey University, 1970)
Five major peptides were isolated by paper electrophoresis from a tryptic digestion of purified fl bacteriophage coat protein. The amino acid composition of the peptides was determined and shown to be:- T1 Ala2, Glu1, Asp2, Pro1, G1yl, Lys1. T2 Al1, Ser1.T3 Phe1, Thr1, Ser1, Lys1. T4 Leu1, Phe1, Lys1. T5 Lys1. Sequential degradation of the intact fl coat protein using the Edman technique showed the N-terminal sequence to be:- Ala - Glu - Gly - Asp - Asp - T1:- The sequence of the tryptic peptide T1 indicated it was derived from the N-terminal of the protein and was assigned the sequence:- Ala - Glu - Gly - Asp - Asp - (Pro1,Ala1) - Lys. T2:- After two cycles of the Edman degradation reaction the sequence of T2 was shown to be:- Ala - Ser Digestion of the intact f1 coat protein with carboxypeptidase A indicated T2 was the C-terminal peptide since carboxypeptidase A showed the C-terminal sequence to be:- - Lys - Ala - Ser T3:- Thin peptide was shown to have the sequence:- Phe - Thr - Ser - Lys T4:- This peptide was assigned the sequence Leu - Phe - Lys T5:- T5was shown be a free Lys residue.
Keywords: Amino acid sequence; Bacteriophage f1 -- Genetics